Synthesis of superparamagnetic Co–Pt nanoparticle in Pyrococcus furiosus virus-like particle crystal. (October 2022) - Taniguchi, Makoto; Higashiura, Akifumi; Kobayashi, Naoto; Kanda, Daisuke; Tagata, Kakeru; Fukunishi, Ryota; Yoshikawa, Yasunori; Kuromatsu, Emi; Kishida, Noriaki; Kotani, Yoshinori; Toyoki, Kentaro; Nakamura, Tetsuya; et al.
Abstract: Superparamagnetic Co–Pt nanoparticles were synthesized in crystal composed of Pyrococcus furiosus virus-like (PfV) particles, a protein with a cage-like structure. Synchrotron X-ray diffraction measurements at the Pt L III edge for the PfV crystal and analysis of Pt anomalous differences revealed that the electron density originated from Pt atom appeared at the 5-fold symmetric site of PfV by soaking Co 2+ and PtCl4 2 −, which did not for the PfV crystal without the soaking. Although the change in electron density extracted by the difference in the anomalous scattering factor at the Co K edge was undetected, we confirmed that Co 2+ was incorporated into the PfV crystal from the experimental result of the X-ray fluorescence spectrum at the Co K edge. Co–Pt nanoparticles were successfully formed by reducing the PfV crystal soaked by Co 2+ and PtCl4 2 − . Transmission electron microscope observation revealed that the average diameter of the synthesized particles was approximately 3.6 nm. Magnetization measurements showed that the synthesized particles were in the superparamagnetic state with a blocking temperature of approximately 50 K at 25 Oe. Highlights: Magnetic Co–Pt nanoparticles are synthesized in protein, Pyrococcus furiosus virus-like Particle (PfV) crystal. Ferromagnetic element (Co) can be incorporated in the PfV by alloying with Pt. The incorporated nanoparticles exhibit the superparamagnetism at room temperature.